2019
DOI: 10.1115/1.4043441
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of the Shoulder Kinematic Chain on Joint Kinematics and Musculotendon Lengths During Wheelchair Propulsion Estimated From Multibody Kinematics Optimization

Abstract: Multibody kinematic optimization is frequently used to assess shoulder kinematics during manual wheelchair (MWC) propulsion, but multiple kinematics chains are available. It is hypothesized that these different kinematic chains affect marker tracking, shoulder kinematics, and resulting musculotendon (MT) lengths. In this study, shoulder kinematics and MT lengths obtained from four shoulder kinematic chains (open-loop thorax-clavicle-scapula-humerus (M1), closed-loop with contact ellipsoid (M2), scapula rhythm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Upper-limb kinematics and subject kinetics were reported for ascending slope propulsion as well as, to a lesser extent, for curb and cross-slope, but not for ground types. Yet, when reported, methodological differences in kinetic and kinematic acquisition (opto-electronic motion capture system, system based on inertial measurement units) and in data processing (musculoskeletal model used for computation of joint angles and moments [ 66 , 67 ], point and basis of expression of net joint moments [ 68 , 69 ]) hinder rigorous comparisons of studies on the same barrier, and prevent the formulation of a reliable evidence-based synthesis of the propulsion biomechanics for each barrier. Lastly, poor data acquisition accuracy may lead to improper conclusions, especially for kinematics and kinetics quantities [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upper-limb kinematics and subject kinetics were reported for ascending slope propulsion as well as, to a lesser extent, for curb and cross-slope, but not for ground types. Yet, when reported, methodological differences in kinetic and kinematic acquisition (opto-electronic motion capture system, system based on inertial measurement units) and in data processing (musculoskeletal model used for computation of joint angles and moments [ 66 , 67 ], point and basis of expression of net joint moments [ 68 , 69 ]) hinder rigorous comparisons of studies on the same barrier, and prevent the formulation of a reliable evidence-based synthesis of the propulsion biomechanics for each barrier. Lastly, poor data acquisition accuracy may lead to improper conclusions, especially for kinematics and kinetics quantities [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental studies have reported the mean residual error on the marker positions [9], and a large range of residual values was found (4-40 mm) according to the complexity of the kinematic chain model (e.g., upperlimb or full-body model), the degree of personalization as well as the movement of interest. Marker reconstruction residuals have been considered a criterion for accuracy in bone and joint kinematics, with the underlying assumption that a better kinematic chain would result in smaller marker reconstruction errors [69]. For systematically evaluating MKO models, Begon et al [9] have recommended ensuring that the marker residuals remain within the STA range reported in the literature [23].…”
Section: Reconstruction Residualsmentioning
confidence: 99%